AB1056 SYMPTOMATIC SCLEROSING MESENTERITIS REVEALING ERDHEIM-CHESTER DISEASE: A RARE CONDITION MEDIATED BY BRAF. (2nd June 2020) - Razanamahery, J.; Humbert, S.; Malakhia, A.; Emile, J. F.; Cohen, F.; Haroche, J.; Magy-Bertrand, N.
Abstract : Background: Sclerosing Mesenteritis (SM) refers to an entire spectrum of digestive inflammatory disorders. Diagnosis is based on imaging showing an increase of fat attenuation displacing bowel loops and is in most cases non-symptomatic. Several conditions (abdominal trauma/surgery, neoplasia, infectious and inflammatory diseases) are responsible for SM (1). Among neoplasia, Erdheim-Chester disease (ECD) is a rare clonal histiocytosis characterized by long bone involvement, peri-nephric fat infiltration and cardio-vascular involvement associated with compatible histology (2). Biopsy is mandatory to confirm tissue infiltration by histiocytes and detect somatic mutation. Almost 80% of ECDpatients harbor mutation in mitogen activated protein (MAP ) kinase pathway especially BRAF V600E gene mutation in about 60% of cases(3). No series of patients presenting both pathologies has been reported. Furthermore, no correlation with BRAF mutation status has been described in patient harboring SM and ECD. Objectives: To describe the clinical, radiological and mutational status of patients harboring SM and ECD. Methods: We reviewed the database of patients with histiocytic disorders in Besancon University Hospital. Patient required one abdominal computed tomography showing sclerosing mesenteritis and clinical/histological features of ECD to fulfill the inclusion criteria. All biopsy samples were investigated for mutation of MAP kinase pathway gene. Results: Four patients suffered from SM and ECD. The median age at the diagnosis of ECD was 68 years old (61-72). All patients described abdominal pain and the mean duration between first symptoms and diagnosis of ECD was 12 months (4-19). The mean CRP level at diagnosis was 40.75 mg/L (5-117). Two patients were found to have myeloid neoplasms (chronic myelomonocytic leukemia (#2) and essential thrombocythemia (#4)) concurrent with ECD diagnosis. Regarding abdominal computed tomography, all patients had a mesenteric mass associated with hyper-attenuated mesenteric fat and a "fat halo sign". One patient (#2) had ascites and one had splenomegaly (#4) but no patient had enlarged lymph nodes. CT also demonstrated peri-nephric fat infiltration ("hairy kidney") (4/4), vascular sheathing of aortic branches (3/4), adrenal hypertrophy (1/4) or ureter dilation (1/4). The mean SUVmax of the mesentery was 7.5 (4.1-10.9) at diagnosis on ( 18 F)- fluorodeoxyglucose-PET. Three patients underwent mesentery fat biopsy and all samples exhibited ECD histology. Regarding mutational status, 75% (3/4) patients had BRAF V600E mutation. After initiation of therapies for ECD (targeted therapies for ¾ patients), all patients had improvement of digestive symptoms and decreased of SUVmax on evaluation 18 FDG-PET during the follow up. Conclusion: ECD should be investigated in patient with symptomatic SM especially if it is associated with peri-nephric fat infiltration. This condition is rare and might be driven by BRAF gene. References: [1]Danford CJ, Lin SC, Wolf JL. Sclerosing Mesenteritis. Am J Gastroenterol. 2019 Jun;114(6):867–73. [2]Diamond EL, Dagna L, Hyman DM, Cavalli G, Janku F, Estrada-Veras J, et al. Consensus guidelines for the diagnosis and clinical management of Erdheim-Chester disease. Blood. 2014 Jul 24;124(4):483–92. [3]Haroche J, Cohen-Aubart F, Rollins BJ, Donadieu J, Charlotte F, Idbaih A, et al. Histiocytoses: emerging neoplasia behind inflammation. Lancet Oncol. 2017 Feb;18(2):e113–25. Disclosure of Interests: None declared